Masculinity, Poststructuralism, and Recovery: Moving beyond Theory to Practice. (October 2019) - Ferkul, Sean
This article seeks to explore how poststructural theory can be applied to therapeutic spaces to evoke conversations around masculinity and identity. By breaking down complicated language and creating accessibility of ideas, poststructural theory has a variety of uses at the practical level. This article provides an entry point for how frontline workers can begin to apply poststructural language to begin exploring complicated themes of identity.